Synthesis, structure revision, and absolute configuration of (+)-didemniserinolipid B, a serinol marine natural product from a tunicate Didemnum sp. - Kiyota, H; Dixon, D; Luscombe, C; Hettstedt, S; Ley, S (2002)
[structure: see text] En route to proving the absolute and relative stereochemistry, through synthesis, of (+)-didemniserinolipid B (1), the first natural serinolipid isolated from a tunicate Didemnum sp., it was discovered that the isolated natural product was in fact the 31-sulfate configured 8R,9R,10R,13S,30S. This structural reassignment was only possible after the development of a microwave-assisted method for the sulfation of unreactive hydroxyl groups.